Supportive Caregiver Communication in Enhancing Adolescent Self-Esteem in Residential Care - Mohammad Ali Fikri; Ananda Dwitha Y; Muhammad Syaamil D; Vira Hawa Aprilila (Universitas Prof. Dr. Moestopo (Beragama), 2026)
Adolescents living in orphanages are vulnerable to low self-esteem due to experiences of loss, family separation, and psychosocial challenges. This study aims to examine how supportive caregiver communication contributes to the development of adolescent self-esteem at the Muhammadiyah Children Centre (MCC) KH. Mas Mansyur. Guided by Social Support Theory, this research employed a sequential explanatory mixed-methods design by combining quantitative and qualitative approaches. Quantitative data were collected using the Rosenberg Self-Esteem Scale (RSES) administered to 19 adolescents, while qualitative data were obtained through semi-structured interviews with 4 caregivers. The findings indicate that adolescents generally demonstrated relatively healthy levels of self-esteem, although differences appeared between male and female participants. The study identified 4 caregiver communication practices: proactive and empathetic interaction, the development of a family-like community, fair and consistent discipline, and positive narrative reframing. These practices reflect emotional, instrumental, informational, and appraisal support that strengthen adolescents’ self-liking and self-competence. The study concludes that supportive caregiver communication plays an important role in fostering adolescents’ psychological well-being and self-esteem within residential care.